Hierarchical Porous Graphene–Iron Carbide Hybrid Derived From Functionalized Graphene-Based Metal–Organic Gel as Efficient Electrochemical Dopamine Sensor - Vermisoglou, Eleni C.; Jakubec, Petr; Malina, Ondřej; Kupka, Vojtěch; Schneemann, Andreas; Fischer, Roland A.; Zbořil, Radek; Jayaramulu, Kolleboyina; Otyepka, Michal (Frontiers in Chemistry, 2020)
A Metal-Organic Gel (MOG) similar in constitution to MIL-100 (Fe) but containing a lower connectivity ligand (5-aminoisophthalate) was integrated with an isophthalate functionalized graphene (IG). The IG acted as a structure directing templating agent, which also induced conductivity of the material. The MOG@IG was pyrolyzed at 600 °C to obtain MGH-600, a hybrid of Fe/Fe3C/FeOx enveloped by graphene. MGH-600 shows a hierarchical pore structure, with micropores of 1.1 nm and a mesopore distribution between 2-6 nm, and BET surface area amounts to 216 m2/g. Furthermore, the MGH-600 composite displays magnetic properties, with bulk saturation magnetization value of 130 emu/g at room temperature. The material coated on glassy carbon electrode can distinguish between molecules with the same oxidation potential such as dopamine in presence of ascorbic acid and revealed a satisfactory limit of detection and limit of quantification (4.39×10-7 M and 1.33×10-6 M, respectively) for the neurotransmitter dopamine.